PENGARUH PENGGUNAAN METODE EVERYONE IS A TEACHER HERE TERHADAP MOTIVASI BELAJAR - Nurul Ainiyah; Darmiany Darmiany; Siti Istiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
In a learning process, students are often found sleepy, busy with themselves, less involved in the learning process, and less confident. This is due to the different basic motivational encouragement of students, so we need a method that can foster student learning motivation as a whole, namely the Everyone is a Teacher here method. The purpose of this study was to find the effect of using the Everyone is a Teacher here method on the learning motivation of fifth grade students of SDN Inpres Soroafu for the 2020/2021 academic year. This type of research is an experiment with the type of pre-experiment design type one group pretest-posttest. The subjects in this research were all fifth grade students in one class with a total of 15 students. Student learning motivation data were obtained from questionnaire data filled in by students and then analyzed using paired sample t-test with the help of the SPSS 16.0 for windows program with a significance level (2-tailed) <0.05. The results of data analysis show a significant value (2-tailed) 0.00 <0.05, it can be concluded that H_a is accepted and H_0 is rejected. The H_a in this study is